Cinema, theory, and political responsibility in contemporary culture - McGee, Patrick, 1949- (Literature, culture, theory, 1997)
This 1997 book explores the political significance of aesthetic analysis in the context of cultural studies. It applies the theories of Adorno, Derrida, and Lacan to film studies, and asks how political responsibility can be reconciled with the concept of the university as a democratic institution. Art and the university, Patrick McGee claims, share a common feature: they are commonly regarded as autonomous realms that resist the determination of economic and political interests, while still playing a crucial role in ethical and political discourse. Through detailed reference to Neil Jordan's film The Crying Game, McGee shows how film can be both a product and a critique of the culture industry. He goes on to analyse the function of the university in producing interpretations of such highly political art forms and in determining the limits of critical discussion. McGee links Adorno with Derrida to provide a new route through cultural studies and the claims of political criticism.